Development of a Biosensor Based on Angiotensin‐Converting Enzyme II for Severe Acute Respiratory Syndrome Coronavirus 2 Detection in Human Saliva - Moreira, Geisianny; Casso-Hartmann, Lisseth; Datta, Shoumen Palit Austin; Dean, Delphine; McLamore, Eric; Vanegas, Diana (Frontiers in Sensors, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the novel coronavirus responsible by COVID-19. Infection in humans requires angiotensin-converting enzyme II (hACE2) as the point of entry for SARS-CoV-2. PCR testing is generally definitive but expensive although it is highly sensitive and accurate. Biosensor-based monitoring could be a low-cost, accurate, and non-invasive approach to improve testing capacity. Herein, we develop a capacitive hACE2 biosensor for intact SARS-CoV-2 detection in saliva. Laser-induced graphene (LIG) electrodes were modified with platinum nanoparticles. The quality control of LIG electrodes was performed using cyclic voltammetry. Truncated hACE2 was used as a biorecognition element and attached to the electrode surface by streptavidin-biotin coupling. Biolayer interferometry was used for qualitative interaction screening of hACE2 with UV-attenuated virions. Electrochemical Impedance Spectroscopy (EIS) was used for signal transduction. Truncated hACE2 binds SARS-CoV-2 wild type and its variants with greater avidity than human coronavirus (Common cold virus). The limit of detection (LoD) is estimated to be 2,960 copies/mL. The detection process usually takes less than 30 minutes. The strength of these features makes the hACE2 biosensor a potentially low-cost approach to screening SARS-CoV-2 in non-clinical settings with high demand for rapid testing (for example, schools, airports).